Pengaruh Investasi, Ekspor, dan Tenaga Kerja terhadap Pertumbuhan Ekonomi di Indonesia - wibow, eka putri julianti; Wibowo, Eka Putri Julianti; Pramukty, Rachmat (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2023)
Previous research or accurate research is needed for a scientific research or artukel. This previous research or accurate research aims to predict the discussion and dominance of variable relationships to Economic Growth in Indonesia. This observation intends to recognize the factors that influence Economic Growth in Indonesia, namely Exports, Investment, and Labor, Literature Review of International Business Economics. The writing of this study serves to solve the theory of influence between variables for future research. The results of this research and discussion of Literature Review are Exports, Investment, and Labor have an impact on Economic Growth in Indonesia.